2017
DOI: 10.1007/s10461-017-1743-4
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of HIV Prevention Information Delivered Through Established Geosocial Networking Mobile Applications to Men Who Have Sex With Men

Abstract: Geosocial networking (GSN) applications could disseminate HIV prevention information to thousands of men who have sex with men (MSM); however, acceptability of the type of information, methods, and frequency of information delivery are unknown. Acceptability of these constructs were assessed through a survey of 224 MSM at the Milwaukee Pridefest. All types of information were found acceptable. A sexual health section and self-seeking information were the most acceptable method and frequency of delivery. Demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Global guidance has recommended the integration of digital technology as a strategy to enhance the reach and effectiveness of HIV prevention efforts among MSM and TW [ 36 , 60 ]. Numerous acceptability studies have identified that MSM would be willing to use phone- and web-based technologies for HIV prevention [ 39 , 40 , 61 , 62 ]. Recent systematic reviews have explored the potential of digital technology to advance various HIV priorities among MSM and other key populations [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Global guidance has recommended the integration of digital technology as a strategy to enhance the reach and effectiveness of HIV prevention efforts among MSM and TW [ 36 , 60 ]. Numerous acceptability studies have identified that MSM would be willing to use phone- and web-based technologies for HIV prevention [ 39 , 40 , 61 , 62 ]. Recent systematic reviews have explored the potential of digital technology to advance various HIV priorities among MSM and other key populations [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 Recently, the use of apps for mobile devices has increased by 90%, representing 77% of the total time spent by people using digital media. 2 From 2009 to 2013, an increase in the use of these apps was observed. In 2013, 40% of men who have sex with men reported that Strengths and limitations of this study ► This systematic review and meta-analysis will combine the results of different studies that have comparable effect sizes and can be computed.…”
Section: Introductionmentioning
confidence: 99%
“…2 3 Mobile applications (apps) with global positioning system (GPS) capabilities allow users to expand their contacts on social networks; they are able to view profiles, send messages, make friends and find partners for the purpose of sexual encounters. 2 The use of apps by people aged 18 years and over increased from 8% in 2005 to 72% in 2013. 4 Recent data indicate that 23%-68% of people in developing countries use the internet, and among these, 77% use sites such as Facebook, Twitter, Instagram, Pinterest and others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis of app-using MSM found that 46% of MSM had CAI with all partners within the previous 3 months, yet as many as 70% of those engaging in CAI had a low self-perceived risk of HIV [ 11 ]. Despite these mixed findings, GSN apps constitute a potential platform for dissemination of HIV prevention-related information or interventions [ 26 ], such as reminders for HIV testing or delivery of home HIV test kits [ 27 , 28 ], identifying locations for HIV testing and treatment centers [ 12 , 18 , 29 ], and recruitment for inclusion in studies of novel HIV prevention and treatment methods [ 16 , 30 ].…”
Section: Introductionmentioning
confidence: 99%